Pre-Service Teachers’ Pedagogic Practices on Recognizing Students’ Characteristics During Practicum - Antoni, Rivi; Mustafa, Jamilah (Interdisciplinary Social Studies, 2023)
Background: Issues about pre-service teachers and their teaching competences have been an endless discussion among Indonesian scholars, especially lecturers in University of Pasir Pengaraian. In teachers training programmes, courses are designed to equip them with competences and knowledge needed in real classrooms. As part of the programme, trainees have to go for a teaching practicum in schools where they can practice pedagogic skills and knowledge in real classrooms. However, though trainees have been equipped with pedagogic competences and knowledge, they still find it difficult to deliver. Thus, it is essential to explore the problems faced by the trainees. Aim: The aim of this study was to investigate further phenomenon that might enlighten the teacher training program in its endeavour to produce competent teachers. Method: For this purpose, the researchers observed and interviewed twelve trainees from Universitas Pasir Pengaraian who were on their practicum. This qualitative case study used rubrics from an observation instrument designed by the teacher’s association of Indonesia. The data were analysed on indicators of pedagogic competences. Findings: The results show that although pre-service teachers were prepared for the practicum, they were not ready in terms of their confidence in teaching, and they experiences adversities to convert the ideas into pedagogic practice. These adversities resulted in them losing their confidence. This finding has impacts on teacher preparation where the university needs to organize the programme to meet the needs of pre-service teachers, the programme per se and to collaborate closely with schools to ensure both parties are involved.